Vicissitudes of Preventive Medicine and a New Challenge - Collen, M. F. (Methods of Information in Medicine, 2002)
Objectives: Significant changes in mortality patterns are part of the changing population demographics. This paper explores their implications for health evaluation and screening programs.Methods: A review of selected age-adjusted mortality rates from the National Vital Statistics Reports of the USA was undertaken and their change over the last five decades analyzed.Results: The review shows a continued decline in mortality rates from leading causes of death, such as heart disease, cancer, stroke, pneumonia and influenza, and a sharp rise in the death rates from Alzheimer’s disease. Available means for detection of Alzeimer’s disease are summarized.Conclusion: Given the emerging possibilities for the treatment and prevention of the progression of Alzheimer’s disease, tests for early detection of Alzheimer’s should be included in health screening examinations.
Keywords: Preventive medicine; vital statistics; dementia; Alzheimer’s disease